Butterfly diversity in different habitats in Simian Mountain Nature Reserve, China (Insecta: Lepidoptera) - Q.-L. Yang; Y. Zeng; Y. Yang; X.-C. Du (SHILAP)
Butterflies, as environmental indicators, can act as representatives for less well-monitored insect groups. In this study, a field survey was conducted in five fixed-distance belt transects during three years. Four indices were used to indicate the butterfly diversity. A total of 3004 individuals of 151 species belonging to 82 genera in 6 families were recorded in the survey. Among them, 67 species were recorded in Simian Mountain for the first time, and Celastrina argiolus (Linnaeus, 1758) was the dominant species; Nymphalidae was the dominant family. Among the five habitats, the species diversity of butterfly in Sample V was the highest, closely followed by that in Sample I in which ecological environment was relatively intact; and the diversity of butterfly in Sample IV, in which human interference was strong, was least. According to our research, the butterfly diversity in habitats with better ecological environments was higher; while the butterfly diversity in habitats with the most intact ecological environment was not the highest; strong human interference could significantly decrease the diversity of butterfly.